Agriculture, Livestock Production and Aquaculture Advances for Smallholder Farming Systems Volume 1 - Kumar, Arvind; Kumar, Pavan; Singh, S. S.; Trisasongko, Bambang Hendro; Rani, Meenu (Cham : Springer International Publishing : Imprint: Springer, 2022)
This two-volume set discusses recent approaches and technological innovations for sustainable agriculture in smallholder farming systems impacted by climate change. The systems covered include crop-based agricultural production, as well as aquaculture and livestock production as related systems using similar techniques to combat food security issues brought about by climate change and resource overuse. The chapters detail innovations involving crop diversification, soil resilience management, geoinformatics and land suitability monitoring for smart farming, information technology in livestock production, and nutrient resource management in fishery aquaculture. Researchers, practitioners and industries will be able to use this information to implement socially and economically sustainable practices to achieve food security in impoverished areas vulnerable to climate change, while also learning about the rapid evolution in information technology that is applicable for and available to small holder farmers. Volume 1 focuses on current innovations in agricultural and livestock practices in response to climate change. It covers the technological challenges, approaches and mitigation strategies encountered by both scholars and practitioners working in livestock and agricultural production systems impacted by climate change.
Chapter1. Impact of future climate change on Agriculture, Livestock Production and Aquaculture: Challenges and Policy -- Chapter2. Managing agricultural nitrogen losses in crop production and mitigation of climate change effects -- Chapter3. Critical analysis and evaluation of groundnut value chain for revamping its production for global food security -- Chapter4. Aluminum uptake, callose accumulation and invertase activity in lowland and upland rice genotypes in related to aluminum stress tolerance -- Chapter5. Gender issues in farming - Challenging socially embedded positions in agrarian context -- Chapter6. Characterization and Appraisal of Crop based Farming System for Sustainable Development of Agriculture -- Chapter7. Nitrogen based for farming system -- Chapter8. Resilience for salt tolerance in rice cultivars using various strategies of conventional breeding, molecular breeding and transgenic approaches -- Chapter9. Geoinformation for land suitability modelling for climate smart farming in Africa -- Chapter10. Climate Change Adaptation: Remote Sensing-based Flood Crop Loss Assessment to Support Crop Insurance -- Chapter11. Smallholder Pig value chains development and livelihood security -- Chapter12. Revolutionizing impact of poultry resources in food security and rural economy -- Chapter13. Milk and Milk Product Safety and Quality Assurance for Achieving Better Public Health Outcomes -- Chapter14. Diversification in Aquaculture Resources and Practices for Smallholder Farmers -- Chapter15. Value addition in meat and fish products for human health and nutrition -- Chapter16. Indian Fish as Bioindicators species -- Chapter17. Conclusion. .
Keywords: Environment; Agriculture; Food security; Sustainability; Environmental Sciences; Agriculture; Food Security; Sustainability